TANGGUNG JAWAB RUMAH SAKIT TERHADAP DOKTER YANG MELAKUKAN KESALAHAN TINDAKAN KEDOKTERAN KEPADA PASIEN - Prasetia Adnyana, Gede; Bela Siki Layang, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013, 2013)
The hospital has an important meaning in providing health care and medical services. The health care and medical services in hospitals is important and should be maintained and improved according to the prevailing standard of services so that the public as consumers can experience the medical services provided. Callings a doctor is one form of health care, so that if a doctor proven to perform mistakes in medical action, the hospital partly responsible for that mistakes made by doctor. Because of the hospital and the doctor has a legal relationship, both were responsible for the health care and medical services that provided to patients. That liability may be criminal liability, civil liability, or liability in the administration law.
Keywords: Responsibilities, Hospitals, Doctors, Medical Action’s Mistakes